Analisis Alih Kode dan Campur Kode pada YouTube Podcast Denny Sumargo: Perspektif Menarik tentang Isu Sosial Budaya - Hananda Suprizka Hasdi; Abdul Azis; Hasriani Hasriani (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to analyze the phenomenon of code switching and code mixing in conversations on the Curhat Bang Denny Sumargo YouTube Podcast which discusses socio-cultural issues. The method used is descriptive qualitative, with data obtained from three relevant podcast episodes. The data were collected through listening techniques and manual transcription, then analyzed using Chaer's theory of code switching and code mixing. Data analysis techniques include data reduction, data presentation in descriptive and tabular form, and inductive inference. The results showed that there were 13 code-switching data, all in the form of external code-switching from Indonesian to English, with no internal code-switching found. In addition, 101 code-mixing data were found, consisting of 37 word insertions, 35 phrase insertions, and 29 clause insertions. The most dominant form of code mix is word insertion because there are many foreign terms that do not have equivalents in Indonesian. The main factors influencing the occurrence of code-switching and code-mixing are the topic of conversation and the speaker's habits while in code-mixing, the habit factor. The findings of this study show that code-switching and code-mixing in the podcast are influenced by the topic of conversation and the linguistic habits of the speakers. This research is expected to enrich sociolinguistic studies, especially in understanding the dynamics of language use in digital media such as podcasts.